INFLUENCE OF SENSORY RETAILING ON CONSUMERS' BUYING BEHAVIOR (International Journal of Food and Nutritional Sciences, 2022)
This study examines the impact of sensory retailing on consumers' buying behavior in restaurants. The researchers collected data from 145 consumers in 10 popular restaurants in Nagercoil Town, using a structured questionnaire with multiple-choice questions. The study found that sensory retailing has a positive influence on consumers' behavior, leading to recommendations, repeat visits, and excitement about specific dishes. However, consumers remain mindful of their limits and budget constraints. The researchers also found that there is a significant difference in sensory experiences based on age groups or monthly income levels. The study concludes that retailers can continue implementing sensory strategies in their restaurants to